Suku Bunga Diturunkan, Investasi Akan Meningkat? - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACTS This paper examines whether reduction in discount rate would spur investment in Indonesia. This analysis is substantial